PREFIX “SE-” IN INDONESIAN - Norkobilov , Murod G‘ayrat O‘gli (Educational Research in Universal Sciences, 2023)
This article describes how the Indonesian language and Uzbek language occupy a place in our lives and aims to reveal the unique qualities of languages.